PENANDA DNA UNTUK ANALISIS GENETIK TANAMAN - . Zulfahmi (Jurnal Agroteknologi, 2013)
Genetic diversity is an important aspect for plant to adapt on environment changes. Information on genetic diversity at individual, species and population levels are required for a basic consideration to formulate strategy conservation and breeding program and utilizing of genetic resources. In the last few decades, the development of DNA based molecular markers techniques has been a significant increase and its are routinely being used in ecological, evolutionary, taxonomical, phylogenetic, population genetic, identification studies of plant sciences. These DNA based markers are distinguished in two types, first non PCR based techniques such as RFLP (Restriction Fragment Length Polymorphism) and second is PCR based techniques such as RAPD (Random Amplified Polymorphic DNA), SSR (Simple Sequence Repeats) and AFLP (Amplified Fragment Length Polymorphism), Cleaved Amplified Polymorphic Sequences (CAPS), Sequence Characterized Amplified Region (SCAR), Single-Strand Conformation Polymorphism (SSCP) and DNA barcoding. These techniques are well established and their advantages as well as limitations have been realized. The review details account of techniques used in identification of markers and their applicability in plant sciences.